THE INFLUENCE OF LEADERSHIP STYLE, WORKLOAD AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE (Case Study on PT. PLN ULP Semarang) - Oka Ndaru Pratama; Kis Indriyaningrum (SEAN Institute, 2022)
The purpose of this study was to determine the effect of Leadership Style, Workload and Career Development on Employee Performance at PT. PLN ULP Semarang. The population in this study were employees of PT. PLN ULP Semarang totaling 232 populasi and only 100 samples from respondents that can be analyzed further. The sampling technique used is probability sampling. The analytical tool used is multiple linear regression then processed using SPSS version 26. The results of this study can be concluded that: (1) Leadership style has no effect on employee performance. (2) Workload has an effect on Employee Performance. (3) Career Development has no effect on Employee Performance.